Antivirulence Genes: Insights into Pathogen Evolution through Gene Loss - Bliven, Kimberly A. (American Society for Microbiology, 2012)
The emergence of new pathogens and the exploitation of novel pathogenic niches by bacteria typically require the horizontal transfer of virulence factors and subsequent adaptation—a “fine-tuning” process—for the successful incorporation of these factors into the microbe's genome. The function of newly acquired virulence factors may be hindered by the expression of genes already present in the bacterium. Occasionally, certain genes must be inactivated or deleted for full expression of the pathogen phenotype to occur. These genes are known as antivirulence genes (AVGs). Originally identified in Shigella, AVGs have improved our understanding of pathogen evolution and provided a novel approach to drug and vaccine development. In this review, we revisit the AVG definition and update the list of known AVGs, which now includes genes from pathogens such as Salmonella, Yersinia pestis, and the virulent Francisella tularensis subspecies. AVGs encompass a wide variety of different roles within the microbe, including genes involved in metabolism, biofilm synthesis, lipopolysaccharide modification, and host vasoconstriction. More recently, the use of one of these AVGs (lpxL) as a potential vaccine candidate highlights the practical application of studying AVG inactivation in microbial pathogens.